2002
DOI: 10.1081/jdi-120004096
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis Management and Predictors for Early Mortality in Uremic Patients Who Die Within One Year After Initiation of Dialysis Therapy

Abstract: Despite improvements in dialysis therapy, the mortality rate of patients with end stage renal disease (ESRD) has remained high. A relatively high proportion of uremic patients dies within one year after the initiation of dialysis treatment. The aim of this study was to evaluate predictors for this early mortality in patients with ESRD. A total of 66 uremic patients were included in the study. Patients were divided in those who survived < 1 year (n = 17) and those who survived > or = 1 year (n = 49). We compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…Studies that were conducted in non-population-based samples of incident patients have reported 90-d mortality rates ranging from 12 (20 -22) (2) were population based, minimizing concerns about selection bias, and both include relatively recent data from patients who initiated HD. The latter point may account for the lower mortality rates as compared with findings from earlier studies, potentially reflecting improvements in pre-ESRD treatment, including earlier referral to a nephrologist, which we and others (30,31) suggest improves survival once on dialysis. It is interesting that patients with diabetes were more likely than patients without diabetes (78.6 versus 72.6%; P Ͻ 0.0001) to receive predialysis care from a nephrologist, but this greater access to care did not seem to explain the unexpected lower 120-d mortality rate that was observed among patients with diabetes.…”
Section: Discussioncontrasting
confidence: 46%
“…Studies that were conducted in non-population-based samples of incident patients have reported 90-d mortality rates ranging from 12 (20 -22) (2) were population based, minimizing concerns about selection bias, and both include relatively recent data from patients who initiated HD. The latter point may account for the lower mortality rates as compared with findings from earlier studies, potentially reflecting improvements in pre-ESRD treatment, including earlier referral to a nephrologist, which we and others (30,31) suggest improves survival once on dialysis. It is interesting that patients with diabetes were more likely than patients without diabetes (78.6 versus 72.6%; P Ͻ 0.0001) to receive predialysis care from a nephrologist, but this greater access to care did not seem to explain the unexpected lower 120-d mortality rate that was observed among patients with diabetes.…”
Section: Discussioncontrasting
confidence: 46%
“…32 Heart failure is the most common cause of early death in patients on dialysis. 33 So, end-stage renal disease patients do not die as often of myocardial infarctions, but rather from sudden cardiac death and congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance data from the United States Renal Data System indicate that the first-year mortality rate has declined in recent years, though it remains elevated relative to later years [3]. To meaningfully reduce poor outcomes during the first year after dialysis initiation, patients must receive appropriate care before dialysis initiation; studies suggest that better care in the predialysis period improves outcomes after initiation, although a recent study raised doubt about the strength of that association [2,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%